Food in Focus: Youth Exploring Food in Schools Using Photovoice - Spencer, Rebecca Ann; McIsaac, Jessie-Lee D.; Stewart, Melissa; Brushett, Sara; Kirk, Sara F.L. (Journal of nutrition education and behavior, 2019)
As part of a study exploring school food environments, this study aimed to understand youth perspectives of school food. Photovoice, a qualitative visual methodology, was used to engage participants through photo-taking, with goals of enabling reflection, promoting dialogue, and facilitating change. Participants were recruited through 2 youth-focused community organizations in Nova Scotia, Canada. Seven youths took part: 3 from a rural area and 4 from an urban center. Youth perspectives on school food environments. The photovoice process of selecting, contextualizing (using the SHOWeD method), and codifying was used for analysis. Four themes were identified. First, spaces and places were important to youth food experiences. Second, key components of food environments were identified as quality, variety, time, and price. Third, the relation between food and social influence was highlighted. Fourth, the importance of amplifying youth voice was discussed. Youth emphasized a desire for greater variety and quality in affordable school food options and the opportunity to be involved in decision-making regarding school food. Future research in other contexts and across larger samples is warranted to extend these findings to help inform stakeholders in school food policy and program implementation.